Formation of "Mahalla Institute" in Uzbekistan as a Local Self-Government Body, Creation of its Legal Foundations (Zien Journal of Social Sciences and Humanities, 2022)
This article outlines the concept of the neighborhood, its history, its importance in the lives of the Uzbek people, as well as the reorganization of a community institution during the years that followed and the founding of it through laws adopted over the years